Regulation of voltage-gated potassium channels attenuates resistance of side-population cells to gefitinib in the human lung cancer cell line NCI-H460. Issue 1 (December 2017) - Choi, Seon; Kim, Hang-Rae; Ryu, Pan; Lee, So
Abstract Background Side-population (SP) cells that exclude anti-cancer drugs have been found in various tumor cell lines. Moreover, SP cells have a higher proliferative potential and drug resistance than main population cells (Non-SP cells). Also, several ion channels are responsible for the drug resistance and proliferation of SP cells in cancer. Methods To confirm the expression and function of voltage-gated potassium (Kv) channels of SP cells, these cells, as well as highly expressed ATP-binding cassette (ABC) transporters and stemness genes, were isolated from a gefitinib-resistant human lung adenocarcinoma cell line (NCI-H460), using Hoechst 33342 efflux. Results In the present study, we found that mRNA expression of Kv channels in SP cells was different compared to Non-SP cells, and the resistance of SP cells to gefitinib was weakened with a combination treatment of gefitinib and Kv channel blockers or a Kv7 opener, compared to single-treatment gefitinib, through inhibition of the Ras-Raf signaling pathway. Conclusions The findings indicate that Kv channels in SP cells could be new targets for reducing the resistance to gefitinib.